Measuring component of integrated information technology design and manufacturing of products with complex geometric configuration - Лещенко, О.О.; Щербак, Л.М. (Proceedings of National Aviation University (archive), 2007)
Use measuring information technologies in modern production - are analyzed. It is made checking the detail on three cuts and is determined deflections of the detail in cut from its mathematical model on example of the concrete detail.